Augmenting neurocognitive remediation therapy to Preventive Cognitive Therapy for partially remitted depressed patients: protocol of a pragmatic multicentre randomised controlled trial. Issue 6 (23rd June 2022) - Bockting, Claudi; Legemaat, Amanda M; van der Stappen, Johanne G J; Geurtsen, Gert J; Semkovska, Maria; Burger, Huibert; Bergfeld, Isidoor O; Lous, Nicoline; Denys, Damiaan A J P; Brouwer, Marlies
Abstract : Introduction: Major depressive disorder (MDD) affects 163 million people globally every year. Individuals who experience subsyndromal depressive symptoms during remission (ie, partial remission of MDD) are especially at risk for a return to a depressive episode within an average of 4 months. Simultaneously, partial remission of MDD is associated with work and (psycho)social impairment and a lower quality of life. Brief psychological interventions such as preventive cognitive therapy (PCT) can reduce depressive symptoms or relapse for patients in partial remission, although achieving full remission with treatment is still a clinical challenge. Treatment might be more effective if cognitive functioning of patients is targeted as well since cognitive problems are the most persisting symptom in partial remission and predict poor treatment response and worse functioning. Studies show that cognitive functioning of patients with (remitted) MDD can be improved by online neurocognitive remediation therapy (oNCRT). Augmenting oNCRT to PCT might improve treatment effects for these patients by strengthening their cognitive functioning alongside a psychological intervention. Methods and analysis: This study will examine the effectiveness of augmenting oNCRT to PCT in a pragmatic national multicentre superiority randomised controlled trial. We will include 115 adults partially remitted from MDD with subsyndromal depressive symptoms defined as a Hamilton Depression Rating Scale score between 8 and 15. Participants will be randomly allocated to PCT with oNCRT, or PCT only. Primary outcome measure is the effect on depressive symptomatology over 1 year. Secondary outcomes include time to relapse, cognitive functioning, quality of life and healthcare costs. This first dual approach study of augmenting oNCRT to PCT might facilitate full remission in partially remitted individuals as well as prevent relapse over time. Ethics and dissemination: Ethical approval was obtained by Academic Medical Center, Amsterdam. Outcomes will be made publicly available. Trial registration number: NL9582.